Entrepreneurship-Based Economic Potential Development in Mekarsari Village, Cibalong District, Garut Regency - Dinihayati, Erti; Mubarokah, Doni Romdon; Sulistyani, Lusiana Ayu; Alamsyah, Kamal; Jusuf, Eddy (International Journal of Science and Society, 2024)
Mekarsari Village, Cibalong District, Garut Regency. Mekarsari Village has a variety of local economic potential that can be utilized to improve the standard of living and welfare of the local community. To make this happen, targeted and sustainable strategic steps are needed. In this article, we identify the economic potential that exists in Mekarsari Village, including natural resources, local expertise, superior products, and market opportunities that can be used as a basis for entrepreneurial activities. Additionally, this article outlines concrete steps that can be taken to encourage entrepreneurial growth in the region. Some of the steps proposed include training and entrepreneurship development programs for village residents, intensive assistance and guidance in the initial stages of business establishment, as well as the formation of cooperatives or joint business groups to strengthen their bargaining position and expand market access. Product diversification, innovation, and effective promotion and marketing are also important parts of the entrepreneurship-based economic development strategy in Mekarsari Village. This service also highlights the importance of collaboration with external parties, such as government agencies, research institutions, universities and private companies, as a means of supporting economic development at the local level. In this context, financial management and accountability are also important factors that need to be considered in order to maintain sustainability and sustainable business growth. Through these structured steps and approaches, it is hoped that this article can provide guidance and inspiration for stakeholders to jointly contribute to advancing the local economy in Mekarsari Village, creating new jobs, and improving the quality of life of the community as a whole.